Investigation of Long-Term Behaviors of Solidified/Stabilized Hazardous Waste Under Different Landfill Conditions - Tombul, Bekir; Kanat, Gurdal; Ozgel, Merve (SPRINGER INT PUBL AG, 2023)
Compared to European Union (EU) countries, the amount of hazardous waste disposed of in Turkey through landfills is 2.5 times greater. The wastes that must be dumped into landfill sites but do not meet the criteria should be pre-treated. The long-term behavior of pre-treated hazardous wastes under landfilled conditions is yet unclear. In this study, a solidified/stabilized flue gas dust from iron and steel production with heavy metal (Ba-Cd-Pb-Zn) contamination was used, and the efficiency of the pre-treatment was examined at a plant in Istanbul. Leak tests and BCR sequential extraction procedure (BCR-procedure) of raw waste and solidified samples were used to characterize the metal phases. Following this, the effect on the different layers of soil and leachate under field (atmospheric) and laboratory (weakly acidic) conditions was monitored by placing the solidified sample in the simulated experimental setup for 321 days. After landfilling, leak tests and compressive strength tests were applied, images were captured with SEM, and physical and chemical evaluations were conducted. According to BCR-procedure, the contamination factor (Cf) and the risk assessment code (RAC) are calculated. The heavy metal Cd had the highest Cf and RAC value for FGD, PLS, FCS, and LCS and the general Cf order was Cd > Zn > Pb > Ba. It has been established that the pH value is more unstable under field conditions; accordingly, metal contamination in soil and leakage samples increases. However, the solidified samples were still found to meet the Turkish landfill waste acceptance criteria following the setting.
Keywords: BCR sequential extraction; Hazardous waste; Heavy metals; Landfilling; Stabilization; solidification; MSWI FLY-ASH; BOTTOM ASH; HEAVY-METALS; STABILIZATION/SOLIDIFICATION; SOLIDIFICATION/STABILIZATION; SPECIATION; LEAD; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources